2008
DOI: 10.1016/j.neuint.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of tetramethylpyrazine on rat retinal cell cultures

Abstract: The retinal degeneration characterized with death of retinal ganglion cells is a pathological hallmark and the final common pathway of various optic neuropathies. Thus, there is an urgent need for identifying potential therapeutic compounds for retinal protection. Tetramethylpyrazine has been suggested to be neuroprotective for central neurons by acting as an antioxidant and a calcium antagonist. In this study, we tested the effects of tetramethylpyrazine on the viability of both neuronal and non-neuronal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Bcl-2 protein family and caspases are intimately associated with the mitochondrial function and progression of the apoptotic events. HN were shown to block pro-apoptotic activities of Bax and Bak proteins [21,39]. It is interesting to note that Bax is not only mitochondrial, but also ERassociated protein [40].…”
Section: Discussionmentioning
confidence: 96%
“…Bcl-2 protein family and caspases are intimately associated with the mitochondrial function and progression of the apoptotic events. HN were shown to block pro-apoptotic activities of Bax and Bak proteins [21,39]. It is interesting to note that Bax is not only mitochondrial, but also ERassociated protein [40].…”
Section: Discussionmentioning
confidence: 96%
“…TMP can protect against MNU-induced retinal damage (17), iron-induced oxidative damage and apoptosis in cerebellar granule cells (18), gastric mucosal injury in a rat model of acute necrotizing pancreatitis, spinal cord ischemia, gentamicin-induced apoptosis in murine renal tubular cells (19), rat asthma, acute liver and lung injury after burn trauma (20), acute myocardium injury after thermal trauma (21) and accelerated anti-glomerular basement membrane antibody nephritis (22). Several studies have also reported that one of the underlying mechanisms of TMP is its reactive oxygen species (ROS)-scavenging activity (21)(22)(23)(24). ROS are also important mediators in the pathogenesis of inflammatory bowel disease (IBD).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear which of Parkin's functions is neuroprotective [55]. Hydrogen peroxide treatment of neuronal and non-neuronal mixed rat retinal cell cultures causes the loss of MAP2 in the neuronal soma, and downregulation of MAP2 increases the vulnerability of retinal neurons to oxidative stress [56].…”
Section: Maps May Act To Protect Neurons Against Oxidative Stressmentioning
confidence: 99%